2003
DOI: 10.1061/(asce)1090-0241(2003)129:4(315)
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction Potential Index: Field Assessment

Abstract: Cone penetration test ͑CPT͒ soundings at historic liquefaction sites in California were used to evaluate the predictive capability of the liquefaction potential index ͑LPI͒, which was defined by Iwasaki et al. in 1978. LPI combines depth, thickness, and factor of safety of liquefiable material inferred from a CPT sounding into a single parameter. LPI data from the Monterey Bay region indicate that the probability of surface manifestations of liquefaction is 58 and 93%, respectively, when LPI equals or exceeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(79 citation statements)
references
References 11 publications
4
67
1
7
Order By: Relevance
“…Toprak and Holzer (2003) found that during the Loma Prieta earthquake in 1989, the median value of LPI for soundings where sand boils occurred was 5, and 25 percent of soundings that showed sand boils had LPI greater than 10. The median value of LPI for soundings where lateral spreading occurred was 12, with 25 percent of soundings that showed lateral spreading having LPI greater than 17.…”
Section: Methods Of Calculation Of Factor Of Safety and Liquefaction Pmentioning
confidence: 99%
“…Toprak and Holzer (2003) found that during the Loma Prieta earthquake in 1989, the median value of LPI for soundings where sand boils occurred was 5, and 25 percent of soundings that showed sand boils had LPI greater than 10. The median value of LPI for soundings where lateral spreading occurred was 12, with 25 percent of soundings that showed lateral spreading having LPI greater than 17.…”
Section: Methods Of Calculation Of Factor Of Safety and Liquefaction Pmentioning
confidence: 99%
“…Bununla birlikte yapılan çalışmada kumlar ve siltli zeminler I c =2.6 değeri ile killerden ayrılmakta ve bu değerin üstündeki zeminler çok fazla oranda kil içerdiğinden dolayı sıvılaşmaz kabul edilmektedir. Ayrıca Sıvılaşma Potansiyeli İndeksine (LPI) göre yapılan analizde de LPI' nın 15' den büyük çıkması durumunda ortamın sıvılaşma açısından riskli olduğu anlaşılmaktadır [18]. Şekil 5' de yapılmış sıvılaşma analizine göre söz konusu inceleme alanında sıvılaşmanın mümkün ve olası olduğu anlaşılmaktadır.…”
Section: Sıvılaşma Analiziunclassified
“…Iwasaki et al (1982) identified that liquefaction effects are moderate for 5 < LPI < 15 and major for LPI > 15. Toprak and Holzer (2003) reported that sand boils occur for LPI ≥ 5 and lateral spreads occur for LPI ≥ 12. Juang et al (2005) studied the effects of liquefaction on the damage of ground surface near foundations.…”
Section: Introductionmentioning
confidence: 99%
“…Juang et al (2005) studied the effects of liquefaction on the damage of ground surface near foundations. LPI shows a clear picture of liquefaction severity during seismic events, and LPI ≥ 5 is generally considered as a threshold for the surface manifestation of liquefaction (Iwasaki et al, 1982;Toprak and Holzer, 2003;Holzer et al, 2006). Sonmez (2003) categorized the sites with LPI = 0 as not likely to liquefy and categorized the sites with 0 < LPI < 2, 2 < LPI < 5, 5 < LPI < 15, and LPI > 15 as having low, moderate, high, and severe liquefaction susceptibility, respectively.İnce (2011) prepared liquefaction susceptibility microzonation map based on LPI for the earthquakes with probability of exceedance of 10 % in 50 yr. Dixit et al (2012) computed FS values for Mumbai city for the earthquakes with return period of 475-and 2475-yr.…”
Section: Introductionmentioning
confidence: 99%